KONSEP KELUARGA MUSLIM DALAM MENJAGA FITRAH SEKSUAL ANAK - Muhammad Rizki Febrian; Syafiq Riza Hasan (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2024)
Islam is a religion that runs according to human nature, so that it has mapped out the rules to fulfill human inner urges, including sexual desire, through the institution of marriage. Islam as a religion of nature is in harmony with the basic nature of humans. The purpose of this study is to dissect the concept of